Editors’ Introduction: Crisis, Connectivity, and the Work of Social Repair in Asia - Asep Iqbal (Journal of Asian Social Science Research, 2021)
Journal of Asian Social Science Research (JASSR), Volume 3, Number 2, 2021, appears in the shadow of the COVID-19 pandemic, yet it is not only a pandemic issue. The pandemic is present as context, pressure, and historical condition, but the articles gathered here are interested in something wider: how societies respond when existing arrangements are tested. They ask how institutions learn, how information systems fail or adapt, how vulnerable groups are included or left behind, how small enterprises mobilize digital tools, and how digital capitalism reorganizes labour and value. This issue is therefore about crisis, but also about connectivity. Connectivity appears as administrative learning through overseas training, as information flow during an infodemic, as the fragile link between people with intellectual disabilities and public services, as online consumption networks for small and medium enterprises, and as platform-mediated labour on YouTube. In each case, connection offers possibility, but never without hierarchy. It can enable coordination and survival, yet it can also reproduce exclusion, misinformation, dependency, and alienation.